Pengaruh Financial Distress, Komite Audit dan Ukuran Perusahaan Terhadap Tax Avoidance : (Studi Kasus pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2020-2022) - Ganda Setyo Prayogo; Ahmad Yani; Rike Selviasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Recently, the Indonesian government has continuously made improvements to the tax system in an effort to maximize revenue from the tax sector. Taxes are a burden for businesses because they limit their ability to generate profits. The aim of this research is to determine the effect of financial distress, audit committee and company size on tax avoidance. This research is associative research, namely research that aims to determine the relationship or influence between two or more variables. The location of this research was carried out in the Sharia Investment Gallery of the Indonesian Stock Exchange at Kadiri Islamic University. The sampling technique in this research used a nonprobability sampling technique with a purposive sampling method which resulted in 39 samples. Researchers in analyzing the data used the SPSS for Windows tool using multiple linear regression analysis methods, classical assumption testing and hypothesis testing. The results of this research show that financial distress (X1) has a significant effect on tax avoidance (Y), the audit committee (X2) has no significant effect on tax avoidance (Y), company size (X3) has a significant effect on tax avoidance (Y), financial distress (X1), audit committee (X2) and company size (X3) have a significant effect on tax avoidance (Y).